Precise aboveground biomass estimation of plantation forest trees using the novel allometric model and UAV-borne LiDAR - Lin, Jiayuan; Chen, Decao; Yang, Shuai; Liao, Xiaohan (Frontiers in Forests and Global Change, 2023)
redwood (DR) trees in the test site. The raw point cloud was first normalized and segmented into individual trees, whose Acs and Hs were sequentially extracted. To mitigate the effects from adjacent trees, the initial Acs were corrected referring to the potential maximum Acs under undisturbed growth conditions. Lastly, the corrected Acs (Acc) and Hs were input into the constructed allometric model to achieve the AGBs of DR trees.Results and discussion: According to accuracy assessment, R 2 and RMSE of extracted Hs were 0.9688 and 0.51m; R 2 and RMSE of calculated AGBs were 0.9432 and 10.91kg. The unrestricted growth parts of the tree crowns at the edge of a plantation forest could be used to derive the potential maximum Ac. Compared with the allometric models for AGB estimation relying only on trunk H or on initial Ac and H, the novel allometric model demonstrated superior performance in estimating the AGBs of trees in a plantation forest.